Quality data management software is a tool for driving improvement activities - Börjeskog, Eric (My University, 2020)
The fourth industrial revolution has changed the possibilities for the manufacturing industry during the last decade through digitalisation. Real-time data can be accessed from production processes and monitoring as well as analyses can be made instantly. The data can be used in the proactive work to identify critical parameters before they cause errors. This thesis investigates how a Swedish manufacturing company can digitalise their measurement data by introducing a quality data management software. Through a literature review, an interview study at the case company and a benchmarking study at an industrial leader in the area, this thesis has been conducted. The study shows how the current situation regarding measurement data at the case company has not reached its potential to use it for improving their business due to the lack of an evaluation software as well as lacking IT infrastructure. Though, by implementing a quality data management software and new equipment, the measurement data can be used for visualisation and analyses to drive improvement activities as it becomes digitalised. This makes the use of the data value-adding, which creates a completely new environment where it is easier to base decisions on facts.
Keywords: digitalisation; Industry 4.0; quality data management software; production; smart manufacturing